Global dialogues in the philosophy of religion from religious experience to the afterlife - Nagasawa, Yujin 1975-; Zarepour, Mohammad Saleh ca. 20./21. Jh (Oxford University Press, 2024)
"The philosophy of religion is a discipline that explores a wide range of issues related to religious beliefs and practices. However, the field has historically exhibited a narrow focus, predominantly centreing on the Christian tradition and lacking substantial interaction between philosophers from distinct religious and cultural backgrounds. To address this, Global Dialogues in the Philosophy of Religion includes contributions from eminent scholars that address the world's five major religious traditions: Buddhism, Christianity, Hinduism, Islam, and Judaism. These dialogues delve into the philosophical aspects of religion, covering significant topics, including revelation and religious experience, analysis of faith, science and religion, the foundations of morality, and life and the afterlife. In each section, one of these critical issues is examined by three distinguished philosophers, each specializing in a particular religious tradition. These authors not only present their own perspectives on the subject matter but also respond to the viewpoints of philosophers from other traditions. This dynamic exchange gives readers valuable insight into how philosophical inquiries can be approached from various religious standpoints. This unique collection offers a rich tapestry of ideas and fosters a greater understanding of the philosophical dimensions of religion across diverse cultural and religious contexts."
Keywords: Religionsphilosophie; Religion / Philosophy; Aufsatzsammlung